Controllable fabrication of nanostructured copper compound on a Cu substrate by a one-step route. Issue 21 (6th March 2015) - Wang, Yongqian; Jiang, Tingting; Meng, Dawei; Kong, Junhan; Jia, Hanxiang; Yu, Meihua
<x xml:space="preserve">Abstract</x> Self-assembled nanostructured copper compound whose absorption edge covers the entire visible spectrum was explored amply and processes excellent photocatalytic activity.